Variability of the second internal transcribed spacer of the ribosomal DNA among five Palaearctic species of anopheline mosquitoes. Issue 17 (2004) - , M. Gordeev; I, I. Goriacheva; I, E. Shaikevich; Ejov, M.
No abstract available